Optimization of biguanide derivatives as selective antitumor agents blocking adaptive stress responses in the tumor microenvironment - Narise K; Okuda K; Enomoto Y; Hirayama T; Nagasawa H (Dove Medical Press, 2014)
Kosuke Narise, Kensuke Okuda, Yukihiro Enomoto, Tasuku Hirayama, Hideko Nagasawa Laboratory of Pharmaceutical and Medicinal Chemistry, Gifu Pharmaceutical University, Daigaku-nishi, Gifu, Japan Abstract: Adaptive cellular responses resulting from multiple microenvironmental stresses, such as hypoxia and nutrient deprivation, are potential novel drug targets for cancer treatment. Accordingly, we focused on developing anticancer agents targeting the tumor microenvironment (TME). In this study, to search for selective antitumor agents blocking adaptive responses in the TME, thirteen new compounds, designed and synthesized on the basis of the arylmethylbiguanide scaffold of phenformin, were used in structure activity relationship studies of inhibition of hypoxia inducible factor (HIF)-1 and unfolded protein response (UPR) activation and of selective cytotoxicity under glucose-deprived stress conditions, using HT29 cells. We conducted luciferase reporter assays using stable cell lines expressing either an HIF-1-responsive reporter gene or a glucose-regulated protein 78 promoter-reporter gene, which were induced by hypoxia and glucose deprivation stress, respectively, to screen for TME-targeting antitumor drugs. The guanidine analog (compound 2), obtained by bioisosteric replacement of the biguanide group, had activities comparable with those of phenformin (compound 1). Introduction of various substituents on the phenyl ring significantly affected the activities. In particular, the o-methylphenyl analog compound 7 and the o-chlorophenyl analog compound 12 showed considerably more potent inhibitory effects on HIF-1 and UPR activation than did phenformin, and excellent selective cytotoxicity under glucose deprivation. These compounds, therefore, represent an improvement over phenformin. They also suppressed HIF-1- and UPR-related protein expression and secretion of vascular endothelial growth factor-A. Moreover, these compounds exhibited significant antiangiogenic effects in the chick chorioallantoic membrane assay. Our structural development studies of biguanide derivatives provided promising candidates for a novel anticancer agent targeting the TME for selective cancer therapy, to be subjected to further in vivo study. Keywords: HIF-1, UPR, antiangiogenesis, hypoxia, glucose deprivation